The hero's journey : stories of women returning to education. - O'Shea, Sarah; Stone, Cathy (International Journal of the First Year in Higher Education v.5 n.1 p.79-91 https://doi.org/10.5204/intjfyhe.v5i1.186, 2014)
This article draws upon the metaphor of the 'hero's journey' to further analyse seven stories of women returning to education. These stories have formed the basis of a recent book publication by the authors and are derived from two complementary but separate research studies. None of the women featured in this article have a parent who went to university and all have a number of competing demands in their lives including families, partners and employment. The article both frames the richly descriptive nature of these stories within a heroic metaphor and also indicates how these stories, whilst unique, share common thematic elements and turning points. The article foregrounds these commonalities capturing a universal narrative and also explores how this mythical framework could be used by both educators and students to conceptualise movements within this environment. [Author abstract]